2008
DOI: 10.1038/ncb1716
|View full text |Cite
|
Sign up to set email alerts
|

RNF4 is a poly-SUMO-specific E3 ubiquitin ligase required for arsenic-induced PML degradation

Abstract: In acute promyelocytic leukaemia (APL), the promyelocytic leukaemia (PML) protein is fused to the retinoic acid receptor alpha (RAR). This disease can be treated effectively with arsenic, which induces PML modification by small ubiquitin-like modifiers (SUMO) and proteasomal degradation. Here we demonstrate that the RING-domain-containing ubiquitin E3 ligase, RNF4 (also known as SNURF), targets poly-SUMO-modified proteins for degradation mediated by ubiquitin. RNF4 depletion or proteasome inhibition led to acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
941
2
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 769 publications
(995 citation statements)
references
References 29 publications
46
941
2
6
Order By: Relevance
“…As SUMO chains are associated exclusively with SUMO2/3 conjugation, this observation indicates that NS1 is likely preferentially SUMOylated by SUMO2/3. SUMO2/3 chains are known to stimulate the polyubiquitination of some SUMOylated proteins, therefore triggering their proteasomal degradation (71)(72)(73)(74). However, our data indicate that SUMOylation does not affect the stability of NS1 (see below).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…As SUMO chains are associated exclusively with SUMO2/3 conjugation, this observation indicates that NS1 is likely preferentially SUMOylated by SUMO2/3. SUMO2/3 chains are known to stimulate the polyubiquitination of some SUMOylated proteins, therefore triggering their proteasomal degradation (71)(72)(73)(74). However, our data indicate that SUMOylation does not affect the stability of NS1 (see below).…”
Section: Discussioncontrasting
confidence: 54%
“…Importantly, for certain substrates, SUMOylation with SUMO2/3 is known to trigger the formation of long poly-SUMO chains that are recognized by ubiquitin ligases and lead to the polyubiquitinylation of the SUMOylated substrate, which in turns leads to their proteasomal degradation (71)(72)(73)(74). Data obtained during the execution of these studies revealed the formation of polySUMOylated NS1 in the presence of wt-ASL and mut-ASL (see, for example, Fig.…”
Section: Ns1 Sumoylation Affects Viral Growth In Ifn-competent and Ifmentioning
confidence: 99%
“…Although different types of stress trigger increases in global SUMO conjugation levels, arsenic very specifically triggers sumoylation of PML (or the PML-RARα fusion). Recent work confirmed that the modified PML then becomes an in vivo target of the STUbL RNF4 [96][97][98][99]. Specifically, ATO-induced PML sumoylation correlates with its subsequent K48-linked polyubiquitination and degradation by the proteasome [100].…”
Section: Pml: Protein Degraded By Sumo-dependent Ubiquitination Pathwaymentioning
confidence: 78%
“…In addition, SUMO-targeted ubiquitin ligases recognize SUMOylated proteins and polyubiquitylate them, targeting them for degradation (Prudden et al, 2007;Sun et al, 2007;Xie et al, 2007;Mullen and Brill, 2008;Weisshaar et al, 2008). Interestingly, PML is the only protein in mammalian cells identified so far that is targeted by the RNF4 SUMOtargeted ubiquitin ligases (Lallemand-Breitenbach et al, 2008;Tatham et al, 2008), and E1A had an observable effect on PML localization that was specifically dependent on binding UBC9 (Figure 6). …”
Section: E1a Interaction With Ubc9mentioning
confidence: 99%